A Graphene Oxide Nano-Sheets: A Novel Eco-Friendly Approach for Tissue Engineering and Antibacterial Applications in Bone Disease - Abdullah, Hind W.; Mubarak, Tahseen H; Resan, Kadhim K. (Science and Technology Indonesia, 2024)
Obtaining novel scaffolds on bone disease-affected cells with osteoconductivity has recently been the focus of tissue engineering methodologies. Chemical treatment and microwave radiation form a novel strategy to create graphene oxide nanosheets (Gns) that decorate carbon crystal structures. This approach is proven to be eco-friendly. Gns was characterized using "X-ray diffraction, ultraviolet, and Fourier transform infrared spectrophotometers". The XRD spectra confirmed the crystalline structure of Gns. The Gns product was analyzed using "Raman spectroscopy. Transmission electron microscopy and field-emission scanning electron microscopy" exposed few layered surfaces of Gns. The TEM images showed Gns specifically decorated with carbon nanoparticles. The evidence demonstrated the novelty of Gns as a very effective bactericidal agent, suggesting its potential as a future antibacterial agent. Different concentrations of Gns and its derivatives showed different cell viabilities toward various cell lines, demonstrating the dependency of a biocompatible environment for good attachment on MG63 cells.